An International Survey Comparing Different Physician Models for Health Care Delivery to Critically Ill Children With Heart Disease. Issue 5 (May 2020) - Bhaskar, Priya; Rettiganti, Mallikarjuna; Sadot, Efraim; Paul, Thomas; Garros, Daniel; Frankel, Lorry R.; Reemtsen, Brian; Butt, Warwick; Gupta, Punkaj
Abstract : Objectives: To explore relationships between the training background of cardiac critical care attending physicians and self-reported perceived strengths and weaknesses in their ability to provide clinical care. Design: Cross-sectional observational survey sent worldwide to 550 practicing cardiac ICU attending physicians. Setting: Hospitals providing cardiac critical care. Subjects: Practicing cardiac critical care physicians. Interventions: None. Measurements and Main Results: We received responses from 243 ICU attending physicians from 82 centers (14 countries). The primary training background of the respondents included critical care (62%), dual training in critical care and cardiology (16%), cardiology (14%), and other (8%). We received 49 responses from medical directors in nine countries, who reported that the predominant training background for attending physicians who provide cardiac intensive care at their institutions were critical care (58%), dual trained (18%), cardiology (12%), and other (11%). A greater proportion of physicians trained in either critical care or dual-training reported feeling confident managing multiple organ failure, neurologic conditions, brain death, cardiac arrest, and performing procedures like advanced airway placement and inserting chest- and abdominal-drains. In contrast, physicians with cardiology and dual-training reported feeling more confident managing intractable arrhythmias, understanding cardiopulmonary interactions, and interpreting echocardiogram, electrocardiogram, and cardiac catheterization. Overall, only 57% of the respondents felt comfortable based on their current training background to manage patients with complex cardiac issues without collaboration with other specialists. Conclusions: Our survey demonstrates that intensivists trained in critical care are more comfortable with critical care skills, cardiology-trained intensivists are more comfortable with cardiology skills, and dual-trained physicians are comfortable with both critical care skills and cardiology skills. These findings may help inform future efforts to optimize the educational curriculum and training pathways for future cardiac intensivists. These data may also be used to shape continuing medical education activities for cardiac intensivists who have already completed their training.